Chlamydial Prevalence, risk factor and complications among symptomatic pelvic inflammatory disease women, visiting hospital - Ammara Iqbal Muhammad; Najeeb, Wajeha; Muskaan Ayaaz (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the prevalence of chlamydia, its risk factors and complications among women with symptomatic pelvic inflammatory disease. Method: The cross-sectional study was conducted from September 2022 to October 2023 at the Gynaecology and Obstetrics Department of a public-sector tertiary care hospital in Rawalpindi, Pakistan, and comprised symptomatic pelvic inflammatory disease women aged 18-50 years. Nucleic acid amplification test on urine samples was used to determine the prevalence of chlamydia. The association with various risk factors was determined. Data was analysed using SPSS version 25. Results: There were 762 women with mean age 27.15±4.43 years (range: 19-49 years). All the participants (100%) were married, with 740(97.1%) being multiparous and 22(2.9%) nulliparous. Of the total, 16(2.1%) women were found to be chlamydia-positive. Among them, 14(87.5%) belonged to lower socio-economic strata. With respect to complications, 1(6.25%) woman had an episode of ectopic pregnancy and infertility. Nulliparous status, aversion to barrier contraception, and age were significant risk factors (p<0.05). Conclusion: The prevalence of chlamydia infection in women with symptomatic pelvic inflammatory disease was low. Increasing age, nulliparity and avoidance of barrier contraception were found to be major risk factors. Key Words: Chlamydia trachomatis, Sexually transmitted diseases, Pelvic inflammatory disease.